Emotional intelligence as a predictor of job satisfaction: the mediating role of conflict management in nurses - Soriano-Vázquez, Iris; Cajachagua Castro, Mayela; Morales-García, Wilter C. (Frontiers in Public Health, 2023)
Background Emotional Intelligence (EI) has emerged as a pivotal factor in work effectiveness and well-being within the healthcare domain. Specifically, its significance is heightened in the nursing sector, where emotional and social demands are high. Additionally, job satisfaction and conflict management are recognized as vital predictors of patient care service quality. However, there is a dearth of research addressing the mediating role of conflict management in the relationship between EI and job satisfaction within a nursing context. Objective This study aims to assess the mediating role of conflict management in the relationship between emotional intelligence and job satisfaction among nurses. Methods The STROBE checklist for cross-sectional studies was followed. A cross-sectional and explanatory design was employed. Data were collected using self-reported questionnaires to measure emotional intelligence, conflict management, and job satisfaction. Structural Equation Modeling (SEM) was conducted to test the proposed hypotheses. Results A total of 208 nurses aged between 18 and 65 years participated (M = 41.18, SD = 8.942). The findings confirmed a positive relationship between emotional intelligence and conflict management (β = 0.64, p < 0.001). Similarly, a positive relationship between conflict management and job satisfaction was observed (β = 0.37, p < 0.001). Moreover, conflict management was validated as a mediator in the relationship between emotional intelligence and job satisfaction (β = 0.77, p = 0.002). Conclusion The study underscores the importance of emotional intelligence and conflict management as predictors of job satisfaction in nurses. The results suggest that interventions aimed at enhancing emotional intelligence might be an effective avenue for increasing job satisfaction, especially when conflict management strategies are integrated.